Apocalypse a natural history of global disasters - McGuire, Bill 1954- (Cassell, 1999)
A discussion of natural disasters which modern society must expect to face in the not too distant future. Each is capable of causing unprecedented disruption to our current cosy way of life. The work provides the reader with the background scientific information needed to understand the phenomena and their effects. This is supplemented by dramatic descriptions of the devastating impact of the catastrophes on society and on the planet itself. The four main sections cover the four likely causes of global catastrophe: volcanoes; earthquakes; tidal waves; and meteoric collisions. There is also a section on how to access relevant information on the Internet.